45.6k views
5 votes
Can someone help me and solve this in a good way it’s really urgent

Can someone help me and solve this in a good way it’s really urgent-example-1
User Narish
by
6.2k points

2 Answers

3 votes

Answer:

4

Explanation:

( 3 + 1/4 a)^2 - 2 ( 3 + 1/4 a)(1 + 1/4 a) + (1+ 1/4 a)^2

= 9 + 3/2 a + 1/16 a^2 - 2( 3 + 3/4 a + 1/4 a + 1/16 a^2) + 1 + 1/2 a + 1/16 a^2

= 9 + 3/2 a + 1/16 a^2 - 6 - 3/2 a - 1/2 a - 1/8a^2 + 1 + 1/2 a + 1/16 a^2

= 4 (answer)

User Jahongir Rahmonov
by
6.5k points
0 votes

We know that :

✿ (p - q)² = (p)² - 2(p)(q) + (q)²

The Given Problem is in the Same Form

Where :


\mathsf{p = (3 + (a)/(4))}


\mathsf{q = (1 + (a)/(4))}


\mathsf{\implies (3 + (a)/(4))^2 - 2(3 + (a)/(4))(1 + (a)/(4)) + (1 + (a)/(4))^2 = [(3 + (a)/(4)) - (1 + (a)/(4))]^2}


\mathsf{\implies (3 + (a)/(4))^2 - 2(3 + (a)/(4))(1 + (a)/(4)) + (1 + (a)/(4))^2 = [(3 + (a)/(4) - 1 - (a)/(4))]^2}


\mathsf{\implies (3 + (a)/(4))^2 - 2(3 + (a)/(4))(1 + (a)/(4)) + (1 + (a)/(4))^2 = [(3 - 1)]^2}


\mathsf{\implies (3 + (a)/(4))^2 - 2(3 + (a)/(4))(1 + (a)/(4)) + (1 + (a)/(4))^2 = [2]^2}


\mathsf{\implies (3 + (a)/(4))^2 - 2(3 + (a)/(4))(1 + (a)/(4)) + (1 + (a)/(4))^2 = 4}

User Alex Santelle
by
5.5k points